Dynamic stability evolution of viscoelastic dielectric elastomers with continuously varying electromechanical parameters. (27th October 2021) - Zhang, Junshi; Tang, Liling; Tang, Dafeng; Liu, Lei
Abstract: Under an actuation of alternating voltage, dielectric elastomer (DE) based actuators are widely utilized as dynamic devices and robots, accompanying with the possible dynamic instabilities. In this article, based on a deduced dynamics model, we develop an analysis on the dynamic performance and stability evolution of a viscoelastic DE, using the continuous method. Effects of mechanical force and applied voltage are considered, respectively. The spectrum of dynamic deformation with the relevant parameters is presented. The evolution of phase paths is simultaneously provided to detect the dynamic stability of the viscoelastic DE.